Kelimpahan Mikroplastik pada Perairan Sumatera Barat: Literature Review - Harmedi Yulian Saputra; Eni Kamal; Abdul Razak (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
The environment is a unity of space that includes all natural elements, including living things and the interactions between these elements. In recent decades, waste pollution, especially microplastics, has become a major threat to aquatic ecosystems and human health. Microplastics are small plastic particles that are dispersed in various aquatic ecosystems and can accumulate in the food chain. This study aims to assess the abundance of microplastics in West Sumatra waters, especially in coastal areas, rivers and lakes. The method used in this research is literature review. Based on the literature review, microplastics were found in sediments and marine organisms, such as fish contaminated by microplastics, with the dominant type being fibers. Some areas, such as Carocok Beach, Bungus Bay and Purus Beach, show high abundance of microplastics, which is associated with human activities and poor waste management. These findings emphasize the importance of better waste management to reduce microplastic pollution. This study also provides a clearer picture of the distribution of microplastics, their impacts on aquatic ecosystems and human health, and suggests more effective plastic waste management policies in West Sumatra to maintain the sustainability of aquatic ecosystems and public health.